¿Qué lugar ocupa hoy la literatura brasileña en América Latina? (Dossier Literatura brasileña y latinoamericana: cruce de lecturas) - Toral Reyes, Santiago (2025)
This article aims to reflect on the position of contemporary Brazilian literature within the current Latin American literary landscape. Drawing on Pascale Casanova’s concept of the “world republic of letters”, it seeks to shed light on the reasons behind the limited presence of Brazilian literature in the broader Latin American literary scene. Although contemporary Brazilian literature has gained some attention due to various sociopolitical events—such as the 2014 World Cup, translation support from the National Library of Brazil, or Brazil’s role as guest country at the 2013 Frankfurt International Book Fair—it is still not widely perceived as part of the Latin American literary whole. This has hindered active exchange between Brazil and Spanish-speaking Latin American countries.